Causes of Informal Payments in Healthcare Services: A Systematic Review - İpek Camuz Berber; Elif Türkan Arslan (Association of Nurse Managers, 2023)
Aim: In this study, it is aimed to reveal the reasons for informal payments in terms of both health service users and health care providers. Method: For this purpose, a search was conducted using the keywords " informal payment", " informal patient payment", "under the counter payment", "under the table payment", "envelope payment", " 'red envelope', 'red package' and 'health' and studies dealing with the causes of resmi olmayan payments were examined. Results: The 14 articles that met the inclusion criteria were extensively reviewed. For the analysis of the data, a standard data collection form was developed by the researchers. In the data collection form, the author(s) of the study, year, purpose, method, sample and sample size, and the reasons for informal payments were included. Studies included in the research by the researchers were summarized according to the form. Conclusion: As a result of the research, it was determined that both service providers (doctor, nurse etc.) and service users (patient-patient relatives) played a role in such payments; It has been observed that service providers demand or accept informal payments mostly for financial reasons, and service users offer such payments because they are afraid of not getting quality/good service and want to provide faster access to services.